PENGARUH PROFITABILITAS, STRUKTUR MODAL, CORPORATE SOCIAL RESPONSIBILITY TERHADAP EARNING RESPONSE COEFFICIENT (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Ema Widiastuti, 13.05.52.0128; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2017)
This study aims to examine and analyze the effect of profitability, capital structure, corporate social responsibility towards earning response coefficient at manufacturing companies listed on the Indonesia Stock Exchange). The population in this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI) from 2013-2015. Sampling technique in this research is done by using purposive sampling method and obtained by total of 144 samples of data observation. The data obtained were analyzed by using multiple linear regression analysis. The results of hypothesis testing can be concluded that (1) Profitability has no effect on earning response coefficient. (2) Capital structure has no effect on earning response coefficient. (3) CSR has a positive effect on earnings response coefficient (ERC), meaning that the higher the disclosure index of CSR information then the earning response coefficient will increase.Keywords: Profitability, Capital Structure, Corporate Social Responsibility and Earning Response Coefficient